Python to Kubernetes: A Programming and Resource Management Framework for Compute-and Data-intensive Applications - Nagiyev, Andrey; Bajrovic, Enes; Benkner, Siegfried (Proceedings - International Conference on Parallel and Distributed Systems, 2024)
In this paper, we introduce the Python to Kubernetes (PTK) framework, a high-level Python-based programming framework for deploying Python applications on top of Kubernetes clusters. PTK supports a task-based programming approach with extensions for specifying resource requirements and performance constraints. A major goal of PTK is to provide users with high-level control for deploying compute- and data-intensive applications on different types and configurations of heterogeneous clusters, while ensuring performance and/or cost constraints.